How to improve your school : giving pupils a voice - Rudduck, Jean.; Flutter, Julia (New York : Continuum, 2007)
This fascinating book focuses on those who are most affected by changes in education policy and systems-the pupils. It draws on empirical evidence from a number of research projects and distils this into a compelling account of contemporary schooling from the pupils' perspective. Jean Rudduck calls for a shift in the way we currently view young people at school and sets out a case for radically rethinking aspects of school organization, relationships and practice. Her research confirms that we need to see pupils differently, to re-assess their capabilities and reflect on what they are capable of being and doing.
Includes bibliographical references
Keywords: School improvement programs; Student participation in administration